2013
DOI: 10.1080/15435075.2011.641187
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks for Predicting Global Solar Radiation in Al Ain City - Uae

Abstract: The geographical location (latitude: 24 • 16 N and longitude: 55 • 36 E) of Al Ain city in the southwest of United Arab Emirates (UAE) favors the development and utilization of solar energy. This paper presents an artificial neural network (ANN) approach for predicting monthly global solar radiation (MGSR) on a horizontal surface in Al Ain. The ANN models are presented and implemented on 13-year measured meteorological data for Al Ain such as maximum temperature, mean wind speed, sunshine, and mean relative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Solar energy is one of the cheap, pollution free, inexhaustible renewable energy resource [6,14,15,16]. Long term detailed knowledge of potential sites is required for the development of this energy resource, in order to establish the solar houses at a large scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar energy is one of the cheap, pollution free, inexhaustible renewable energy resource [6,14,15,16]. Long term detailed knowledge of potential sites is required for the development of this energy resource, in order to establish the solar houses at a large scale.…”
Section: Resultsmentioning
confidence: 99%
“…Pakistan is blessed with huge spectrum of al renewable energy sources with high potential including conventional as well as non-conventional which have not been sufficiently explored, employed or developed. Out of range of renewable energy resources, in coming years one of the cleanest, powerful, cheap, safe and virtually inexhaustible energy source upon which the world can depend is solar energy [6,11,12,13,14,15,16]. Global potential of solar energy is 3,000,000 TWh/y [17].…”
Section: Introductionmentioning
confidence: 99%
“…Using Multilayer Perceptron and Radial Basis Function neural networks with different input parameters, Maitha et al have predicted monthly solar radiation. In this study, they have demonstrated that Radial Basis Function neural network with Absolute Fraction of Variance of 92% gives a better performance in comparison with Multilayer Perceptron neural network [19].…”
Section: Introductionmentioning
confidence: 96%
“…Among the empirical methods, machine learning has been widely used to solve real world problems [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Artificial neural networks (ANNs) are well-known machine learning systems that have been utilized to predict the solar radiation [2][3][4][29][30][31][32][33][34][35][36][37][38][39][40]. As typical examples in this context, Rahimikhoob [41] successfully applied ANN for predicting the global solar radiation.…”
Section: Introductionmentioning
confidence: 99%